OP77 The advance project: an australian national program to support nurses to initiate advance care planning in general practice. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Clayton, J; Nagarajan, S; Lewis, V; Detering, K; Halcomb, E; Tieman, J; Mitchell, G; Phillips, J; Morton, R; Costa, D; Gavin, J; Stokes, J; et al.
Abstract : Background: Primary care has been advocated as an ideal setting to initiate advance care planning (ACP). Few studies have examined the role of general practice nurses (GPNs) in promoting/initiating ACP. The Advance Project evaluated initiatives to address this gap. Methods: This Australian Government-funded program aims to increase GPNs' confidence in initiating conversations with patients/carers about ACP during routine health assessments with older and/or chronically ill patients using a structured interview. This is part of a broader program enabling GPNs to identify patients at risk of deteriorating and dying and to assess these patients' palliative/supportive care needs. Identified needs are then addressed in consultation with General Practitioners. The program includes a suite of resources and multi-component training (online, face-to-face and individual tele-mentoring). Pre/post/follow-up surveys and qualitative interviews collected GPNs' perspectives about the training/resources and barriers to implementation in clinical practice. Results: As of 31 December 2017, 823 GPNs enrolled in training and 536 completed one or more training components. 27 workshops were held across Australia, including 182 regional/rural participants. 585 pre-training, 384 post-training, and 125 follow-up surveys were received. 20 GPNs were interviewed. There were significant improvements in GPNs' confidence, comfort, knowledge and attitudes towards initiating ACP post-training that was sustained at follow-up. Participants were significantly more likely to have had ACP discussions with their patients at follow-up (81%) compared to baseline (55%, p<0.001). Discussion/Conclusion: GPNs can have an important role in initiating ACP. The evaluation informed refinement/expansion of the resources/training to support team-based initiation of ACP in general practice http://www.theadvanceproject.com.au